Human cytomegalovirus in cancer: the mechanism of HCMV-induced carcinogenesis and its therapeutic potential - Yu, Chuan; He, Suna; Zhu, Wenwen; Ru, Penghui; Ge, Xuemei; Govindasamy, Kavitha (Frontiers in Cellular and Infection Microbiology, 2023)
Cancer is one of the leading causes of death worldwide. Human cytomegalovirus (HCMV), a well-studied herpesvirus, has been implicated in malignancies derived from breast, colorectal muscle, brain, and other cancers. Intricate host-virus interactions are responsible for the cascade of events that have the potential to result in the transformed phenotype of normal cells. The HCMV genome contains oncogenes that may initiate these types of cancers, and although the primary HCMV infection is usually asymptomatic, the virus remains in the body in a latent or persistent form. Viral reactivation causes severe health issues in immune-compromised individuals, including cancer patients, organ transplants, and AIDS patients. This review focuses on the immunologic mechanisms and molecular mechanisms of HCMV-induced carcinogenesis, methods of HCMV treatment, and other studies. Studies show that HCMV DNA and virus-specific antibodies are present in many types of cancers, implicating HCMV as an important player in cancer progression. Importantly, many clinical trials have been initiated to exploit HCMV as a therapeutic target for the treatment of cancer, particularly in immunotherapy strategies in the treatment of breast cancer and glioblastoma patients. Taken together, these findings support a link between HCMV infections and cellular growth that develops into cancer. More importantly, HCMV is the leading cause of birth defects in newborns, and infection with HCMV is responsible for abortions in pregnant women.